2009
DOI: 10.1007/978-3-642-04268-3_80
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Form Jensen-Renyi Divergence for Mixture of Gaussians and Applications to Group-Wise Shape Registration

Abstract: In this paper, we propose a generalized group-wise non-rigid registration strategy for multiple unlabeled point-sets of unequal cardinality, with no bias toward any of the given point-sets. To quantify the divergence between the probability distributions -specifically Mixture of Gaussians -estimated from the given point sets, we use a recently developed information-theoretic measure called Jensen-Renyi (JR) divergence. We evaluate a closed-form JR divergence between multiple probabilistic representations for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Formally, we compute the Jensen-Renyi (JR) divergence [15] between the set of images for a single place represented as intensity histograms. The JR divergence evaluates the cumulative dissimilarity between two point sets (histograms in our case).…”
Section: Measuring Intrinsic Naturementioning
confidence: 99%
“…Formally, we compute the Jensen-Renyi (JR) divergence [15] between the set of images for a single place represented as intensity histograms. The JR divergence evaluates the cumulative dissimilarity between two point sets (histograms in our case).…”
Section: Measuring Intrinsic Naturementioning
confidence: 99%
“…The JRD is a convenient objective function in that it can also be applied to the task of registration as investigated by a number of reports. 38,39,48 This may facilitate future work involving the simultaneous segmentation and registration of multimodality images using this metric in order to reduce computation time and improve accuracy of both processes. Such an algorithm would have great application towards IGART where previous plan contours provide a good approximation for initialization.…”
Section: -10mentioning
confidence: 99%
“…Some studies have observed that the JRD is more robust to image noise than mutual information when applied to registration as long as the weighting parameters are chosen appropriately. 38,39 Mutual information is a common objective function for registration tasks, and while it is not commonly used for segmentation, it is based on entropy terms which a number of authors have investigated for use in segmentation. [40][41][42][43] The use of entropy based on intensity value histograms (in particular using nonparametric density estimates) is an effective objective for statistically based segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…After construction of the probability density functions, registration reduces to the computation of transformation parameters minimizing the distance between these density functions. Thereto, several information-theoretic measures are used such as KullbackLeibler (KL) divergence [14], Kernel Correlation [11], the L2-norm [7,10], Jensen-Shannon Divergence [13] or Jensen-Renyi Divergence [12]. Due to their independence to point correspondences, some of these methods are inherently robust against outliers.…”
Section: Introductionmentioning
confidence: 99%